The film preservation guide : the basics for archives, libraries, and museums (National Film Preservation Foundation, 2004)
Includes bibliographical references (p. 109-113) and index. Available electronically via WWW in PDF format at http://www.filmpreservation.org/preservation/film%5Fguide.html